The Effect of Resistance Band And ABC Drill Exercises on The Frequency And Speed of Scrick Kicks of Pencak Silat Athletes Puslatcab Pagar Nusa Surabaya City - Amirulloh Karim; Afif Rusdiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research was based on my visit to Puslatcab Pagar Nusa, Surabaya City, at that time the athletes were practising sparring and I saw a lack of speed in their crescent kicks. The purpose of this study was to determine the effect of Resistance Band and ABC Drill training on the Frequency and Speed of crescent kicks of Puslatcab Surabaya City athletes. This study used an experimental method with a